Characteristics of Central Nervous System (CNS) Involvement in Children With Non-Hodgkin's Lymphoma (NHL) and the Diagnostic Value of CSF Flow Cytometry in CNS Positive Disease. (31st May 2021) - Huang, Shuang; Jin, Ling; Yang, Jing; Duan, Yanlong; Zhang, Meng; Zhou, Chunju; Zhang, Yong-Hong
Objective: To investigate the characteristics of central nervous system (CNS) involvement in children with non-Hodgkin's lymphoma (NHL) and the value of flow cytometry (FC) in the diagnosis of CNS disease in pediatric NHL. Methods: The data of 56 newly diagnosed pediatric NHL patients with CNS involvement (CNS+/mass, CNS+/palsy, CNS+/CSF) were analyzed. The proportions and formats of CNS disease in different pathological types were compared. In addition, FC and conventional cytology (CC) of cerebrospinal fluid (CSF) were carried out in 383 newly diagnosed NHL cases. Results: A total of 383 children with NHL were enrolled. Among these patients, 56 (14.6%) were diagnosed with positive CNS involvement (CNS+), 33 had bulky disease (tumor diameter >10 cm), 32 had bone marrow invasion, 32 had lactate dehydrogenase levels >1000 U/L, and 25 had invasion of more than 4 organs at the time of diagnosis. There were 14 patients with T lymphoblastic lymphoma (T-LBL), 9 with B lymphoblastic lymphoma (B-LBL), 26 with Burkitt's lymphoma (BL), and 2 with Epstein-Barr virus-positive diffuse large B cell lymphoma (EBV + DLBCL). Among the 56 CNS+ patients, 35 were CSF-positive (CSF+); there were 2 patients who were CSF+ via CC detection and 35 who were CSF+ via FC detection. The difference between CC and FC was statistically significant ( P < 0.01). In the T-LBL group, 14 patients were CNS+/CSF, and in the B-LBL group, 8 were CNS+/mass. In the BL group, 22 patients were CNS+/mass and 15 were CNS+/CSF. In the anaplastic large-cell lymphoma group, 5 patients were CNS+/mass. Nine of the 56 CNS+ patients had events. The 2-year overall survival rate was 87% ± 0.046%, and the 2-year event-free survival rate was 76.2% ± 0.07%. Conclusion: CNS+ diagnoses were more common in pediatric NHL patients with bulky disease and/or bone marrow involvement and/or involvement of more than 4 organs at the time of diagnosis, and they were also common in the EBV + DLBCL and BL groups. FC of CSF showed important clinical significance in the diagnosis of CNS disease in pediatric NHL patients, and it can be used to significantly improve the CNS+ detection rate.